Replacement of Soybean Meal With Soybean Cake Reduces Methane Emissions in Dairy Cows and an Assessment of a Face-Mask Technique for Methane Measurement - Silveira, Sylvia Rocha; Terry, Stephanie Amelia; Biffin, Tamara Elaine; Maurício, Rogério Martins; Pereira, Luiz Gustavo Ribeiro; Ferreira, Alexandre Lima; Ribeiro, Rafael Sandin; Sacramento, João Paulo; Tomich, Thierry Ribeiro; Machado, Fernanda S.; Campos, Mariana. M.; Gama, Marco Antonio Sundfeld; et al. (Frontiers in Veterinary Science, 2019)
The objective of this study was to a) evaluate the effect of replacing soybean meal (SBM) with soybean cake (SBC) on feeding behavior, rumen fermentation, milk production, nutrient digestibility and CH4 emissions and b) investigate whether a face-mask technique could be used to predict daily methane (CH4) emissions in dairy cattle. The experiment was conducted as a completely randomized design, with 32 crossbred Holstein × Gyr cows (days in milk (DIM): 112 ± 25.1) randomly assigned to the following treatments (n = 8/group) for 75 days: 1) 0 % SBC, 2) 6 % SBC, 3) 14 % SBC, and 4) 23 % SBC, in place of SBM on a dry matter (DM) basis. Across the final 4 weeks of the study, CH4 production was estimated using the proposed face-mask technique subsequent to a respiration chamber measurement for an evaluation of treatment efficacy and face-mask accuracy. There was no effect of SBM replacement by SBC on intake, feeding or drinking behavior (P>0.21). Total VFA concentration, the individual proportions of VFA and blood metabolites were not altered (P>0.17) by SBC, however there was a tendency for decreased (P = 0.08) lactate and plasma urea nitrogen (P=0.07) concentration associated with SBC addition. Fat-corrected milk yield (FCM4%) and composition was not affected (P>0.27) by SBC; however, there was a tendency for decreased total milk solids (P=0.07) and milk fat (P = 0.08) associated with 23% SBC treatment. There was no treatment × technique interaction (P > 0.05) effect on gas measurements. A maximum reduction (P=0.01) in CH4 yield (g/kg DM) and intensity (g/kg milk) of 11 and 20 %, respectively, was observed for the 14 % SBC inclusion. Compared to the week of mask measurements, chambers decreased (P=0.01) intake (kg/d, %BW) and increased (P=0.05) FCM4%. The face-mask method over estimated O2 consumption by 5%. The face-mask method accurately predicted daily CH4 emissions when compared to the chamber at the same time-point. However, there was a linear bias of CH4 outputs so further evaluation of the calculation of total CH4 from a spot measurement is required.